The influence of peripheral-bone-removal protocol on bone augmentation in dental implant surgery: 5-year clinical retrospective study - Alhamdani, Faaiz; Hassan, Ahmad Fliah; Al-Nuaimy, Amaal (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Bone augmentation aims to provide sufficient bone volume around dental implants. Available bone augmentation methods include autogenous bone grafts, xenografts, and alloplastic materials. All have their advantages and disadvantages. However, autogenous bone graft remains the gold standard for bone augmentation. Autogenous bone grafts are usually taken from the patient’s oral donor sites such as the chin and mandibular ramus. However, there is a newly developed implant preparation protocol, known as the peripheral-bone-removal (PBR) technique, which can provide bone augmentation from the dental implant site. Purpose: This study aims to determine the need for bone substitute materials in the PBR technique in dental implant surgery. Methods: This study included 130 patients who were treated for dental implants. These patients were treated between 7.1.2018 and 3.2.2023. Six dental implant systems were used. Five of these systems (ImplantKa®, DeTech®, NeoBiotech®, Easy Implant®, and Dentaurum® Implant) used a conventional method (sequential drilling technique). The sixth (IBS®) system used the PBR protocol. Both descriptive and Chi-Square Test statistics were used for data analysis. Results: The included patients were treated with a total of 198 dental implants. Seventy patients were treated with the PBR protocol, while 60 patients were treated with the sequential drilling protocol. For the PBR protocol, only 2 cases required bone substitute material, whereas 11 cases treated with the sequential drilling protocol required augmentation materials. This difference between both drilling protocols has been statistically confirmed (P=0.008). Conclusion: The PBR technique appears to be less traumatic and more cost-effective for cases that require horizontal bone augmentation.